Esophagitis and Gastritis - Recent Updates 2021
DOI: 10.5772/intechopen.96296
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal Lesions Associated with Portal Hypertension: An Extensive Review

Abstract: The block of the portal flow by obstacles in prehepatic, hepatic or posthepatic site and alterations of the splanchnic blood flow are the pathological conditions that lead to portal hypertension. The portal hypertension can cause also others gastroduodenal lesions, potentially hemorrhagic, in addition to esophageal varices commonly developed and habitual source of bleeding in these patients. The gastroduodenal lesions associated with portal hypertension, usually encountered in the clinical practice, are portal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Eventually, the gastric mucosa becomes more prone to injury by noxious agents such as non-steroidal anti-inflammatory drugs and H. pylori, ending up with erosions, ulcers, and bleeding. 5,9 In our study, we reported the spectrum of lesions of gastric mucosa by endoscopy and histopathology in patients with portal hypertension and correlate these findings to upper gastrointestinal (GI) bleeding. WLE is the diagnostic modality for gastric mucosal lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, the gastric mucosa becomes more prone to injury by noxious agents such as non-steroidal anti-inflammatory drugs and H. pylori, ending up with erosions, ulcers, and bleeding. 5,9 In our study, we reported the spectrum of lesions of gastric mucosa by endoscopy and histopathology in patients with portal hypertension and correlate these findings to upper gastrointestinal (GI) bleeding. WLE is the diagnostic modality for gastric mucosal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal barrier weakening produced by portal hypertension-related mucosal hemodynamic alterations and exposure to noxious substances can be described as two key contributors. 5 Helicobacter pylori (H. pylori), a spiral gramnegative bacteria that is resistant to gastric juice, infects roughly 50 -70 % of the world population, with the highest frequency in low-income areas. It was found to exacerbate local gastric inflammatory response through release of inflammatory cytokines resulting in a wide range of gastric pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that reported decreased mucosal blood flow [21][22][23][24], similarly there are others who reported the reverse [25][26][27][28][29]. Severity of histological and gross morphological changes are related to degree and duration of portal hypertension [30][31][32]. Altered gastric haemodynamics possibly induce activation of various cytokines and growth factors.…”
Section: Portal Hypertensive Gastropathymentioning
confidence: 93%
“…Altered gastric haemodynamics possibly induce activation of various cytokines and growth factors. Gastric mucosa in PHG is reported to contain increased vascular endothelial growth factor [32,33]. Tumour necrosis factor is implicated to play a major role in the pathogenesis of PHG for increase blood to gastric mucosa by stimulating nitric oxide (NO) production by inducing NO synthase.…”
Section: Portal Hypertensive Gastropathymentioning
confidence: 99%
See 1 more Smart Citation